2010
DOI: 10.1021/jz1010994
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Dynamics of Methyl Acetate in Methanol

Abstract: The H-bond interactions of methyl acetate in methanol have been studied by means of ab initio molecular dynamics simulations within the Car−Parrinello approach. It has been observed that the CO stretching band of methyl acetate splits into a doublet as a consequence of the interaction with the solvent. The H-bond effects on the spectroscopic properties of methyl acetate in methanol have been interpreted by wavelet transform analysis in conjunction with a structural and dynamic characterization of the solvatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 20 publications
(45 reference statements)
2
49
0
Order By: Relevance
“…However, for MA the slope of the straight line, which is proportional to μ 2 , increases with the number of H-bonds. As indicated (Table 1), the trend is in qualitative agreement with a previous theoretical study, 34 which showed that upon H-bond formation the transition dipole moment of the C=O stretching vibration of MA is increased. 39 For EA, the transition dipole moments were found to be similar for the 0hb and 1hb species, whereas formation of two H-bonds slightly decreases the transition dipole moment (see Table 1).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, for MA the slope of the straight line, which is proportional to μ 2 , increases with the number of H-bonds. As indicated (Table 1), the trend is in qualitative agreement with a previous theoretical study, 34 which showed that upon H-bond formation the transition dipole moment of the C=O stretching vibration of MA is increased. 39 For EA, the transition dipole moments were found to be similar for the 0hb and 1hb species, whereas formation of two H-bonds slightly decreases the transition dipole moment (see Table 1).…”
Section: Resultssupporting
confidence: 91%
“…33 Their results indicate that H-bond formation with the solvent can lead to a significant decrease in the vibrational lifetime of this mode, which is in agreement with the current study. In addition, Righini and coworkers 34 have used ab initio molecular dynamics simulations to show that such H-bonds have a lifetime of 0.5 to 2 ps. Here, we expand the scope of these previous studies by further characterizing the chemical exchange kinetics between differently H-bonded states of MA and EA molecules in methanol under equilibrium conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm adopted to compute wavelet transform W n ( s ) in the Fourier space is expressed as 22 where ω k is the angular frequency for the k th normal mode and F̂ k and ψ̂ are the Fourier transformations of the time series F n and the mother wavelet ψ( t ), respectively. The mother wavelet ψ( t ) is represented aswhere the parameters ω 0 and σ are set as reported elsewhere.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…On the other hand, MD simulation provides one of the most direct ways to theoretically investigate the molecular behavior [29], which is not accessible to experimental approaches in complex systems, such as a system involving H-bond interactions [30]. Furthermore, in order to obtain useful insight into the H-bond dynamics, it is important to establish the correlation between the simulation results of structural or vibrational properties and experimental measurement results [31].…”
Section: Introductionmentioning
confidence: 99%